Identification and analysis of single nucleotide polymorphisms (SNPs) in citrus - Novelli, V. M.; Takita, M. A.; Machado, M. A. (Kluwer Academic Publ, 2004)
Most of the cultivated species of citrus have narrow genetic basis. Relationships among species and cultivars are obscured by sexual compatibility, polyembryony, apomixis and a high incidence of somatic mutations. DNA analysis is crucial in genetic studies not only for citrus breeding programs but also for characterization of hybrids and species. In this paper, single nucleotide polymorphisms ( SNPs) were investigated in 58 accessions of Citrus, hybrids and related genera. Genomic sequences of 'Pera IAC' sweet orange ( Citrus sinensis L. Osbeck) were used for primer design and selection of sequence tagged sites (STSs) for identification of SNPs. Analysis of 36 STSs showed identical sequences among 40 of the 41 sweet orange accessions studied. However, these accessions were heterozygous for many SNPs. Ten selected STSs were analyzed in 17 additional accessions from 13 species and hybrids. Comparing to the 'Pera IAC' sweet orange accession, a total of 150 polymorphic nucleotides were identified and most of the alterations were transitions ( 52.7%). The greatest number of SNPs was observed in Poncirus trifoliata ( L.) Raf. and the smallest in 'Ponkan' mandarin ( Citrus reticulata Blanco). At the intra-specific level, 'Bafa Gigante' ( Citrus sinensis L. Osbeck) was the only sweet orange accession with a divergent SNPs genotype, which corroborates the hypothesis of a hybrid origin for this accession. Although the STSs analyzed represent randomly sampled genomic sequences, they provided consistent information about the level of polymorphism and showed the potential of SNPs markers for characterization and phylogenetic studies.
Keywords: characterization; DNA polymorphism; germplasm; molecular markers